Time to stop playing: No game studies on a dead planet - Hammar, Emil L.; Jong, Carolyn; Despland-Lichtert, Joachim (Eludamos: Journal for Computer Game Culture, 2023)
This article highlights the interrelated crises that the games industry, its digital game consumers, and the academic field of game studies are embedded in and responsible for reproducing. By couching our analysis in Marxist, feminist, anti-fascist, and anti-imperialist understandings of how our social relations arise from the historical-material basis of society, we identify several different conditions of modern digital games that everyone working in and around games should confront and take seriously, especially regarding contemporary and future impacts and restrictions on the type of research and education we are able to conduct. These crises emerge from social and economic structures including imperialism, racism, militarism, fascism, and patriarchy. To better confront them, we broadly define the causes from which the morbid symptoms we witness arise in primarily Western societies and how they manifest in the games industry, its consumers, and its academic institutions. Based off these aspects, we extrapolate their trajectory in how they will change and adapt to the future of games and of their study, as the ecological and social crises intensify and reverberate. This allows us to propose potential strategies for radically confronting and potentially overcoming the looming crises related to war, patriarchy, white supremacy, famine, destitution, fascism, and climate apocalypse.